Do leitor participante ao repórter cidadão: as implicações do novo ato de ler e colaborar no webjornalismo: uma análise do canal leitor-repórter - Chaise, Maria Joana Chiodelli (Universidade do Vale do Rio dos Sinos, 2010)
The information and communication technologies have motivated the urgency for new relationships between the subjects and the media. The Internet, especially the web 2.0, introduced the issue freedom and the exchange of subjects. Any individuals with access to the net got conditions to produce and spread information, at any given time and place. This scenario, which has a meaningful contribution within the increasing mobility of subjects record technologies, gives a new status to the collaborators / readers. However, on web newspapers, the possibilities for readers to be incorporated to the process of journalistic production are pre-defined and limited. At the same time they invite the audience to participate, these media follow the holders of sense protocol of the enunciations. By the means of selection and mediation processes, they decide to include the contents or not, even in participating or collaborative channels. This research investigated the interagents' collaborations in the online participating journalism Reader-Reporter, from reference web newspaper zerohora.com. Through a subject analysis, it was aimed to understand, on one side, the readers' motivations to send collaborative materials to the section and, on the other side, to assess the selection or mediation of subjects process carried out by the channel editing professionals. The logics that rule the behavior of the actors that are involved in this negotiation are analyzed based on their intersection with the codes of the conventional or collaborative journalism. Besides tracing a profile of the readers' contributions in the collaborative channel, the study also investigated the process that is triggered within the web newspaper in order to have a collaboration published. The outcomes show that the participative online journalism practiced through the Reader-Reporter section has achieved with limits the status of democratization tool and, in short, represents an additional channel for information reception, mostly underestimated by the web newspaper editorial staff.
Keywords: Jornalismo; Webjornalismo colaborativo; Webjornais de referência; Mediação; Leitor-repórter; Collaborative journalism; Reference web newspapers; Mediation; Reader-reporter; ACCNPQ::Ciências Sociais Aplicadas::Comunicação